Efficacy of a medication management service in improving adherence to tyrosine kinase inhibitors and clinical outcomes of patients with chronic myeloid leukaemia: a randomised controlled trial - Tan, Bee Kim; Chua, Siew Siang; Chen, Li-Chia; Chang, Kian Meng; Balashanker, Sharmini; Bee, Ping Chong (Springer Verlag (Germany), 2020)
Purpose: Suboptimal adherence to tyrosine kinase inhibitors (TKIs) contributes to poor clinical outcomes in chronic myeloid leukemia (CML). This randomised controlled trial (RCT) aimed to evaluate the impact of a medication management service (MMS) on adherence to TKIs and clinical outcomes. Methods: A parallel RCT was conducted in two hospitals in Malaysia, where 129 CML patients were randomised to MMS or control (usual care) groups using a stratified 1:1 block randomisation method. The 6-month MMS included three face-to-face medication use reviews, CML and TKI-related education, two follow-up telephone conversations, a printed information booklet and two adherence aids. Medication adherence (primary outcome), molecular responses and health-related quality of life (HRQoL) scores were assessed at baseline, 6th and 12th month. Medication adherence and HRQoL were assessed using medication possession ratio and the European Organisation for Research and Treatment in Cancer questionnaire (EORTC_QLQ30_CML24) respectively. Results: The MMS group (n = 65) showed significantly higher adherence to TKIs than the control group (n = 64) at 6th month (81.5% vs 56.3%; p = 0.002), but not at 12th month (72.6% vs 60.3%; p = 0.147). In addition, a significantly higher proportion of participants in the MMS group achieved major molecular response at 6th month (58.5% vs 35.9%; p = 0.010), but not at 12th month (66.2% vs 51.6%; p = 0.092). Significant deep molecular response was also obtained at 12th month (24.6% vs 10.9%; p = 0.042). Six out of 20 subscales of EORTC-QLQ30-CML24 were significantly better in the MMS group. Conclusions: The MMS improved CML patients’ adherence to TKI as well as achieved better clinical outcomes. Trial Registration: Clinicaltrial.gov (ID: NCT03090477). © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.